Selective ABO immunoadsorption in hematopoietic stem cell transplantation with major ABO incompatibility. (7th June 2021) - Crysandt, Martina; Soysal, Hatice; Jennes, Eva; Holtick, Udo; Mrotzek, Matthias; Rehnelt, Susanne; Holderried, Tobias A. W.; Wessiepe, Martina; Kunter, Uta; Wilop, Stefan; Silling, Gerda; Gecht, Judith; et al.
Abstract: Objective: ABO mismatch between donor and recipient occurs in 40% of allogeneic hematopoietic stem cell transplantations (HCT). Different strategies have been described to reduce isohemagglutinins (IHA) before HCT. We describe the effect of selective ABO immunoadsorption (ABO IA) on erythrocyte transfusion rate and the development of post‐transplant pure red cell aplasia (ptPRCA). Methods: 63 patients with major ABO incompatibility were retrospectively analyzed. Nine patients with major ABO incompatibility and high‐IHA titer were treated by ABO IA before HCT. We analyzed the need for transfusion and the occurrence of ptPRCA. We compared the outcome with patients treated by other methods to reduce IHA. Results: In all nine patients treated by ABO IA, IHA decreased in a median four times. PtPRCA occurred in one patient. The median number of transfusions was 8 (range: 0‐36) between d0 and d100. In 25 patients with high‐IHA titer without treatment or treated by other methods to reduce IHA, the need for transfusions was comparable. No difference in the incidence of ptPRCA was observed. Conclusions: Selective ABO IA is a feasible, safe, and effective method to reduce IHA before HCT in major ABO incompatibility. No effect on transfusion rate or ptPRCA compared to other strategies could be observed.